2007
DOI: 10.1159/000103661
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Biliary Leakage after Partial Liver Resection Using Topical Hemostatic Agents

Abstract: Liver resection is widely accepted as the only potentially curative treatment in malignant or benign hepatobiliary lesions. Although not frequent, biliary leakage is a postoperative complication which may have considerable consequences. The field of topical hemostatic agents is rapidly developing, with various products currently available. This article reviews the risk factors associated with biliary leakage and the methods used for testing or prevention of biliary leakage. A literature search was performed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 43 publications
2
29
0
1
Order By: Relevance
“…Most studies from North America, Europe, and East Asia reported rates of moderate and severe dementia ranging between 3 and 7% for populations over 65 years of age [14]. However, worldwide, the prevalence rates of dementia in different studies vary from very low (0.62%) in Kolkata, India, for a population aged 50 years and more [15], to very high in Israel (19.2%) in a population aged 65 years and more [16]. Whatever the true prevalence turns out to be, it is clear that rates of dementia increase steeply and dramatically with age.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies from North America, Europe, and East Asia reported rates of moderate and severe dementia ranging between 3 and 7% for populations over 65 years of age [14]. However, worldwide, the prevalence rates of dementia in different studies vary from very low (0.62%) in Kolkata, India, for a population aged 50 years and more [15], to very high in Israel (19.2%) in a population aged 65 years and more [16]. Whatever the true prevalence turns out to be, it is clear that rates of dementia increase steeply and dramatically with age.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for bile leakage are high-risk procedures with exposure of the major glissonian sheath [3,4,26,28], resections combined with bilioenteric anastomosis [29,30], size of resection plane [26], patient age [28], higher preoperative white blood cell count [28], and prolonged operation time [3,28]. In a retrospective series of more than 600 patients, Capussotti et al [4] showed an association between the application of fibrin sealant on the resection surface and a lower incidence of bile leakage (RR = 0.38, p = 0.046).…”
Section: Fibrin Sealants and Prevention Of Bile Leakagementioning
confidence: 99%
“…Biliary leakage may lead to intraperitoneal septic complications, liver failure and ultimately, death [3]. The incidence and management of bile leakage after partial liver resection in our Department from 1992 to 2004 has been reported by Erdogan et al [4,5]. However, the management of this complication has changed from relaparotomies to mainly non-surgical interventions in the last years, potentially leading to a decrease in procedure-related complications and better outcomes.…”
Section: Introductionmentioning
confidence: 99%